TRANSFORMASI MEDIA TRADISIONAL: KEUNTUNGAN MENGGUNAKAN FLIPBOOK DIGITAL DALAM PEMBELAJARAN DI SEKOLAH DASAR - Afifah Dwi Rahmadhani; Nurhafizah lubis; Abdullah Taufik Ritonga; Nunu Mahnun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The transformation of learning media from paper and statistical presentations to digital interactive formats has become an important part of efforts to improve mutual teaching and student engagement. One form of innovation that has emerged is the digital flipbook. This study aims to examine the advantages or positive impacts of using flipbooks in learning through a systematic literature review approach with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method. The search strategy was carried out through databases such as Google Scholar, Scopus, and ScienceDirect with the keywords "flipbook", "advantages", and "elementary school students". The selected articles were selected based on certain inclusion and exclusion criteria, including publications in the last five years, empirical studies, and the context of flipbook use in learning at the elementary level. From the screening results, several studies were obtained showing that the use of AR can increase student engagement, strengthen reading comprehension, and spark interest in material literacy. This study concludes that Augmented Reality is a learning medium that can provide advantages or positive impacts for students, although further, more in-depth research is needed to measure its long-term impact